Fostering Student Participation Through Interactive Teaching in Basic English Class - Siane Indriani (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2016)
The purpose of the study was to examine the 1st semester teacher college students’ perceptions of the interaction between them and their teacher in Basic English class through class discussion interactive teaching in Basic English class. To create a successful and effective teaching, cooperation between teacher and students is needed. An effective teacher must be able to present their material, effectively manage their classroom according to the lesson they’ve planned, accommodate their students’ needs, and enhance their students’ participation in the learning activities. Participants were 25 students who reported their perceptions on the interactive teaching in addition to their learning process. Result suggested that the interactive teaching fostered student participation during the learning activities. Teaching method such as class discussion that involved the whole class participation to raise questions and discuss about the answer or solution would require interaction between teacher and students more intensively. This interactive teaching method could be implemented for college students, especially because they were expected to participate more actively in the learning activities and become more independent learners. This study could also be an alternative for any educational practitioners who would like to foster their students’ participation.